Elaboration and acceptability of playful material for children in treatment in a blood center during the COVID-19 pandemic (Research, Society and Development, 2022)
This study aims to describe the development and acceptability of a specific playful material used as a mediating resource in children’s care at a blood center during the COVID-19 pandemic. Considering the profile of the children assisted in the service, predominantly with sickle cell disease, we invested in the production of playful materials representing red blood cells (HbA and HbS), white blood cells, bone marrow, and the SARS-CoV-2 virus. The models were inspired in existing versions, except for the bone marrow, and we chose to make them in crochet and to add human aspects, such as mouth and eyes, for better acceptance and assimilation of the material by the children. The blood elements were used in the treatment of new and ongoing cases, inserted in the psychological intervention. The stylized model of the virus was used to produce educational videos about prevention and care during the pandemic, which were sent to the families of children in follow-up and disseminated in social networks. The results indicate the viability and receptivity of the playful material by patients, parents and health providers, and reinforce the importance of providing creative resources as support for the treatment and management of the chronic diseases in children.